2008
DOI: 10.1681/asn.2007040401
|View full text |Cite
|
Sign up to set email alerts
|

A Switch in the Mechanism of Hypertension in the Syndrome of Apparent Mineralocorticoid Excess

Abstract: The syndrome of apparent mineralocorticoid excess arises from nonfunctional mutations in 11␤-hydroxysteroid dehydrogenase type 2 (11␤HSD2), an enzyme that inactivates cortisol and confers aldosterone specificity on the mineralocorticoid receptor. Loss of 11␤HSD2 permits glucocorticoids to activate the mineralocorticoid receptor, and the hypertension in the syndrome is presumed to arise from volume expansion secondary to renal sodium retention. An 11␤HSD2 null mouse was generated on an inbred C57BL/6J genetic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 51 publications
3
57
2
Order By: Relevance
“…Inhibition of 11b-HSD2 by carbenoxolone was shown to enhance the heart rate in rats (Zhang et al 2006). Furthermore, urinary catecholamine levels were double in 11b-Hsd2 K/K mice (Bailey et al 2008). Thus, the increased blood pressure following UNX might be the consequence of both an enhanced renal sodium retention and an increased sympathetic drive, a hypothesis of interest as it is conceivable that the dampened renal efferent nerve activity to the contralateral kidney after UNX modulates the 11b-HSD activity in the remaining kidney (Recordati et al 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Inhibition of 11b-HSD2 by carbenoxolone was shown to enhance the heart rate in rats (Zhang et al 2006). Furthermore, urinary catecholamine levels were double in 11b-Hsd2 K/K mice (Bailey et al 2008). Thus, the increased blood pressure following UNX might be the consequence of both an enhanced renal sodium retention and an increased sympathetic drive, a hypothesis of interest as it is conceivable that the dampened renal efferent nerve activity to the contralateral kidney after UNX modulates the 11b-HSD activity in the remaining kidney (Recordati et al 2000).…”
Section: Discussionmentioning
confidence: 96%
“…30,31 NCC activity is regulated by several neurohormonal systems, including the sympathetic nerves,angiotensin II, glucocorticoids, sex steroids, vasopressin, and insulin. 32 There is controversy regarding the influence of mineralocorticoids, the dominant regulators of chronic Na + balance.…”
Section: Namentioning
confidence: 99%
“…We therefore concentrated our studies on mice at 60 days of age, reasoning that any process contributing to DCT hypertrophy remained active at this age and that previous work had confirmed that hypertension in our model is largely driven by renal Na + retention at this age. 31 Increased Total and Phosphorylated NCC in the Plasma Membrane Immunoblotting of whole-kidney homogenates was used to estimate the abundance of NCC and of the specific phosphorylated forms of NCC that are associated with NaCl transport activity. Total NCC and the phosphorylated forms pT53, pT58, and pS71 were more abundant in Hsd11b2 2/2 kidneys than in the wild types ( Figure 4A).…”
Section: Accelerated Epithelial Proliferation In the Dctmentioning
confidence: 99%
See 2 more Smart Citations